Modern Korea - Grajdanzev, Andrew J. (International Secretariat, Instituteof Pacific Relations, 1944)
Contents: This book was begun when there was still complete silence about Korea on the international scene. It has been completed at a time when Korea has come into the news. The heads of the American, British and Chinese Governments at their meeting in Cairo in November 1943 expressed their determination that "in due course" Korea would become free and independent. The day that happens this book, written about contemporary Korea, will become a book about her past; I will be the first to rejoice at this change.